Dinamika Resiliensi Komunitas dan Ekonomi melalui Inovasi Kelembagaan Koperasi Tunda Tebang Kelompok Tani Hutan Jasema - Aldina Himmarila Muliawati; Sabda Apriliana Budiatmadja; Azarine Malika Zayyan; Salma Darajatun; Aisya Alifarizki; Nova Dewi Soraya; Fano Alfian Ardyansyah; Muhammad Rafi Gunadi (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The exploitative practice of premature logging, locally known as the "tebang butuh" (need-based logging) phenomenon driven by household economic pressures, has long posed a structural threat to the sustainability of community forest ecosystems in the karst region of Terong Village, Bantul Regency. Responding to these ecological and financial vulnerabilities, the Jasema Forest Farmer Group (Kelompok Tani Hutan or KTH) initiated an institutional innovation in the form of the Delayed Logging Cooperative (Koperasi Tunda Tebang or KTT) using an Asset-Based Community Development (ABCD) approach. This study comprehensively evaluates the effectiveness of the community’s cultural, ecological, and economic transition using the Sustainable Livelihood Approach (SLA) framework to examine the needs across five livelihood capitals. Adopting a pure descriptive qualitative research design with a phenomenological case study approach, this research explores sociological meanings and empowerment dynamics through in-depth interviews with 23 key informants, KTT board members, and community forest farmers, alongside participatory observation, Focus Group Discussions (FGDs), and ICCTF document analysis. The findings indicate that the ABCD approach implemented through the KTT successfully reduces poverty vulnerability by leveraging local potential as its primary pillar. The cooperative provides microcredit facilities collateralized by agreed-upon standing live trees, gradually severing the cycle of land degradation caused by dependency on selling premature timber to middlemen. This transition in forest governance is proven to enhance ecological resilience by preserving carbon-sequestering tree stands while restoring household economic resilience. This capacity building is fully reflected in the enhancement of social capital grounded in communal trust, increased human capital literacy, the preservation of karst natural capital, the consolidation of physical capital, and the creation of autonomous financial capital circulation. Ultimately, this forest farmer community initiative represents an inclusive, adaptive, and sustainable model of rural community empowerment.